Edukasi tentang Anemia pada Remaja Putri di Dayah Terpadu Al Madinatuddiniyah Syamsuddhuha Kecamatan Dewantara Kabupaten Aceh Utara - Jasmiati Jasmiati; Elizar Elizar; Nurmila Nurmila; Nova Sumaini Prihatin (Jurnal Abdimas Kesehatan (JAK), 2023)
Adolescence is a period when growth occurs rapidly, so nutritional needs also increase. One of the nutrients whose needs increase is iron. Iron deficiency can cause anemia. Failure to reduce anemia can result in millions of women experiencing health and quality of life problems, can interfere with development and learning. Anemia is more common in young women, because it is the age group that needs the most nutrients. The purpose of this community service activity is to increase young women's knowledge about anemia. The problem-solving method used is to provide education about anemia to young women starting with a pre-test followed by delivery of counseling materials about anemia to young women and ending with a post-test and distributing leaflets and posters about anemia. Community service activities carried out for one day at Integrated Dayah Al Madinatuddiniyah Syamsuddhuha, Dewantara District, North Aceh Regency with 30 target audiences, resulted in an increase in knowledge during the pre test in the good category, namely 57% to 87% during the post test after being given counseling about anemia .Participants were enthusiastic about the education delivered, no one left the counseling area, this proved that the participants paid attention to the counseling material delivered. It is expected that health workers and teachers will provide information about anemia to young women as an effort to increase knowledge by activating peers so that information is conveyed to young women continuously so that they can prevent and treat anemia as early as possible.